Novel convergence analysis of narrowband FXLMS-based algorithm - An, Fengyan; Sun, Hongling; Li, Xiaodong (ACAI 2012 : International Conference on Automatic Control and Artificial Intelligence : 3-5 March 2012, 2012)
This paper presents a novel convergence analysis of the narrowband active noise/vibration system with FXLMS-based algorithm. It is revealed that the convergent behaviour mainly depends on the phase error of the secondary path model as well as the structure of the controller. With a constant step size, the convergent speed of the algorithm is maximized at a critical value of the phase error. The algorithm exhibits different convergent behaviours if the phase error is below or above this critical value, respectively. The theoretical analysis is validated by numerical simulations.